INFORMATION POLLUTION, MANIPULATION AND ETHICS IN THE AGE OF TECHNOLOGY AND SOCIAL MEDIA - Saygılı, Neriman (International Online Journal of Education and Teaching, 2023)
The relevance of everything exchanged in the virtual world has grown in tandem with the advancement of technology and its growing presence in human existence. The usage of social media and the speed has risen as the prevalence and availability of information or news among people of the transmitting elements, knowledge, or who needs to know the person or institution with high demand has increased. Messages, both written and augmented with visual features, have expanded the scope of human life's ability to "communicate." Everyone who embraces journalism as a career has used visual components to support it and understands why a news article has an influence on people. In reality, the endeavor to get chosen news articles in front of everyone by complementing the content with visual elements in a virtual environment puts the phrase "manipulation" back to the forefront in the news and in information transfer methods. The application of information pollution methods on information, news, or visual assets in anything from sports to art creates new threats. The most essential element of mainstream media, as is well recognized, is its one-sidedness. However, today's rapidly evolving new media has placed the individual in the role of both transmitter and receiver. Politicians, celebrities, institutions, and organizations all utilize social media, which is mostly used by young people. The issue of accessing news or information, as well as misleading, deceiving, or manipulating the transmission of acquired material, has been highlighted today thanks to social media, whose speed and audience size have reached amazing heights thanks to satellite technology. The virtual world, which is highly entangled in ethical dilemmas, makes us doubt the area's dependability and the correctness of information flow. The challenges of information pollution and manipulation in the virtual world will be investigated utilizing sample news in this study. A survey research developed for senior students of Girne American University’s Faculty of Communication also supports the subject's substance.